2015
DOI: 10.1007/s00580-015-2124-x
|View full text |Cite
|
Sign up to set email alerts
|

Aspartate aminotransferase to platelet ratio index and severity of hepatic fibrosis in children

Abstract: Liver biopsy is the gold standard for detection of the severity of liver fibrosis and cirrhosis. However, it is limited by invasiveness, complications, sampling error, and variability in pathological interpretation. On the other hand, the aspartate aminotransferase to platelet ratio index (APRI) is a good estimator of hepatic fibrosis. This study aims to investigate the association between APRI value and severity of liver fibrosis. Blood samples were taken from 52 patients with the age of 2 months to 18 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…[8,9] APRI has been shown to be useful as a predictor of histological severity as well as for follow-up of liver cirrhosis. [10] In a study conducted in United Kingdom, elevated APRI was shown to be associated with future risk of adverse events, independently and additively of the response to ursodeoxycholic acid (UDCA) therapy. [11] To the best of our knowledge, few studies have investigated noninvasive markers specifically for PBC.…”
Section: Introductionmentioning
confidence: 99%
“…[8,9] APRI has been shown to be useful as a predictor of histological severity as well as for follow-up of liver cirrhosis. [10] In a study conducted in United Kingdom, elevated APRI was shown to be associated with future risk of adverse events, independently and additively of the response to ursodeoxycholic acid (UDCA) therapy. [11] To the best of our knowledge, few studies have investigated noninvasive markers specifically for PBC.…”
Section: Introductionmentioning
confidence: 99%